Diseminasi Pendidikan Islam Moderat Melalui Bimbingan Rohani di Rumah Sakit via Media Sosial di Jawa Timur - Ach. Khatib; Alief Zakil Fuadi (STAI AL-AMIN, 2024)
This study examines the dissemination of moderate Islamic education values through spiritual guidance services to hospital patients using social media platforms during the COVID-19 pandemic in East Java. Patient vulnerability during illness creates opportunities and risks related to religious ideological influence. The research objective is to analyze how hospital spiritual counselors disseminated moderate Islamic education through YouTube, Facebook, and Instagram while maintaining guidance continuity under pandemic health protocols. This qualitative research with library research methodology examined content from RSI A Yani Surabaya and RSI UNISMA Malang during 2020-2021. Data were collected through documentation techniques analyzing 47 YouTube videos, 126 Facebook posts, and 89 Instagram posts. Analysis followed Miles and Huberman's descriptive-analytical framework. Results show spiritual counselors successfully disseminated moderate Islamic education values characterized by tawassuth, ta'adul, and tawazun through digital platforms. YouTube emerged as the primary medium with content demonstrating Ahlus Sunnah wal Jamaah practices including tawassul. Digital transformation expanded spiritual education reach beyond hospital physical limitations. Research confirms the importance of ensuring moderate ideological orientation among hospital spiritual guidance personnel.